(untitled) (Journal of Nuclear Technology in Applied Science, 2025)
This study presents the modification of a high-activity Cobalt-60 irradiator (2 megacuries) to function as a multi-purpose irradiator through the application of radiation physics, shielding penetration analysis, and design engineering. A new safe irradiation trace has been developed to enable experimental irradiation processing alongside mass production operations. The modified design incorporates a maze system that allows experimental products to be placed in two specially designed boxes outside the new maze entrance. These boxes travel through safely engineered maze legs into the interior concrete shielding zone and stop behind the primary product boxes positioned in front of the radiation source rack.Following the predetermined irradiation exposure period, the experimental boxes exit through the newly proposed path. The study details the maze system design, including the calculation of maximum exposure rates at various locations—specifically the outer surfaces of primary concrete shields (walls and roof) and along the trace distances. Monte Carlo simulations were performed to evaluate the redesigned irradiator, which features complex geometrical configurations. Three-dimensional flux distributions were calculated at multiple positions within the irradiator, and gamma volume dose rates were accurately determined. The results support the safety and feasibility of incorporating experimental irradiation processes within the high-capacity gamma irradiator system.